The metamorphic architecture of the transpressional Gondwanide Orogen in southern South America: Insights from P-T-D-t paths. - Oriolo, Sebastián (2021)
Fil: Oriolo, Sebastián. IGEBA (CONICET-Universidad de Buenos Aires). CABA, Argentina.